The Effectiveness of YouTube Learning Videos in Enhancing Students' Comprehension of Procedure Text Structures: A Case Study of Fifth Grade Students - Lenny Gusti Arini; Sutikno; Rahmat Kartolo (PT Inovasi Pratama Internasional, 2026)
This study investigates the effectiveness of YouTube learning videos in enhancing fifth-grade students' comprehension of procedure text structures at UPT SD Negeri 064004 Medan during the 2025-2026 academic year. Initial observations revealed low student comprehension of procedure texts and insufficient variety in teaching media utilized by educators. This qualitative descriptive research involved 22 fifth-grade students who engaged with a YouTube video from the